A Successful Collaboration between an Indigenous Youth Sport Program and Sport Psychology Faculty and Students. Issue 4 (31st October 2022) - Fry, Mary D.; Hogue, Candace M.; Claunch, Joseph; Iwasaki, Susumu
Abstract: The Zuni Youth Enrichment Project (ZYEP) is dedicated to enhancing the quality of life for children living in the Pueblo of Zuni, a rural Indigenous community. Sport and exercise psychology scholars have highlighted the need for greater diversity in applied sport psychology research, arguing specifically for greater exposure to applied work with populations from traditionally underrepresented backgrounds. This paper describes a collaboration between an Indigenous youth program and a sport psychology lab that included the development of a coaching workshop for a sport-based positive youth development program. Collaborative efforts and the coaching workshop activities are shared, along with lessons learned.